Multiparametric Cardiac Magnetic Resonance Survey in Children With Thalassemia Major. (August 2015) - Casale, Maddalena; Meloni, Antonella; Filosa, Aldo; Cuccia, Liana; Caruso, Vincenzo; Palazzi, Giovanni; Rita Gamberini, Maria; Pitrolo, Lorella; Caterina Putti, Maria; Giuseppe D'Ascola, Domenico; Casini, Tommaso; Quarta, Antonella; et al.
<x xml:space="preserve">Abstract</x> Background— Cardiovascular magnetic resonance (CMR) plays a key role in the management of thalassemia major patients, but few data are available in pediatric population. This study aims at a retrospective multiparametric CMR assessment of myocardial iron overload, function, and fibrosis in a cohort of pediatric thalassemia major patients. Methods and Results— We studied 107 pediatric thalassemia major patients (61 boys, median age 14.4 years). Myocardial and liver iron overload were measured by T2* multiecho technique. Atrial dimensions and biventricular function were quantified by cine images. Late gadolinium enhancement images were acquired to detect myocardial fibrosis. All scans were performed without sedation. The 21.4% of the patients showed a significant myocardial iron overload correlated with lower compliance to chelation therapy (P<0.013). Serum ferritin ≥2000 ng/mL and liver iron concentration ≥14 mg/g/dw were detected as the best threshold for predicting cardiac iron overload (P=0.001 and P<0.0001, respectively). A homogeneous pattern of myocardial iron overload was associated with a negative cardiac remodeling and significant higher liver iron concentration (P<0.0001). Myocardial fibrosis by late gadolinium enhancement was detected in 15.8% of the patients (youngest children 13 years old). It was correlated with significant lower heart T2* values (P=0.022) and negative cardiac remodeling indexes. A pathological magnetic resonance imaging liver iron concentration was found in the 77.6% of the patients. Conclusions— Cardiac damage detectable by a multiparametric CMR approach can occur early in thalassemia major patients. So, the first T2* CMR assessment should be performed as early as feasible without sedation to tailor the chelation treatment. Conversely, late gadolinium enhancement CMR should be postponed in the teenager age.